Assessment of hostile intent attributions across escalating conflict stories. Issue 3 (8th December 2022) - Godleski, Stephanie A.; Murray‐Close, Dianna
Abstract: Previous research suggests the importance of intent attributions in the development and maintenance of aggressive behavior. The primary purpose of the current study was to develop a measure assessing increases in attributions of hostility in response to escalating social conflict scenarios that were relational and instrumental in nature and to determine whether hostility trajectories were associated with relevant social experiences and behavior. A sample of primarily emerging adults ( n  = 750; M age = 19.97, SD = 3.60; 49.4% women, 48.3% men, 2.3% nonbinary or transgender; 69.9% Caucasian) responded to surveys regarding social behavior, peer victimization, and reports of hostile attribution biases in addition to the developed measure. Findings indicated that individuals adjusted their intent attributions across the conflict escalation stories, as reflected in linear increases in hostility ratings. Hostile attribution trajectories were also related to hostile attribution biases, peer victimization, and social behavior, including physical and relational aggression and prosocial behavior.